The revitalisation of project management capability maturity in the electricity generation, transmission and distribution industry : the case of ESKOM in the Republic of South Africa - Moepi, Tshepiso Christian (My University, 2020)
This research focuses on the evaluation of the project management maturity at Eskom. The problem is that Eskom struggled with delivery of projects as planned. The main objective of this research was to identify an applicable PMMM to assess the project management maturity level of Eskom’s core business units, namely Transmission, Distribution and Generation, by assessing its capability to undertake projects effectively in order to provide electricity to the Southern Africa communities. A quantitative research methodology was selected. A survey was conducted with a closed-ended questionnaire made up of three parts (Applicable project management maturity model, project management culture and project management organisation strategy maturity). The population consisted of senior project managers, project managers, and related project management personnel from Eskom in MegaWatt Park Johannesburg. 200 questionnaires were distributed to the Eskom business units, namely Distribution, Generation and Transmission project management employees, selected purely on their experience and knowledge, hence purposive sampling was used. Surveys were emailed to the respective project management personnel with the help of the senior manager. 133 were returned. This is a response rate of 66 %, which was deemed acceptable. Descriptive statistics was utilised to assess the project management maturity level of Eskom business units. Statistical Package for Social Sciences version 24 (SPSS) was utilised for the purpose of data and reliability analysis. Correlation and linear regression analysis were undertaken to evaluate influence of maturity levels of organisational strategy and culture on the project management maturity level. A Cronbach’s Alpha was utilised to measure the reliability of the data. It was concluded there were project management process areas, not performing well. Namely: project time management, project cost management and project procurement management. The assessment of project management organisational factors indicated that project management culture maturity did not perform well. It performed under the project management maturity level of Eskom. The recommendations of this study are that the applicable project management maturity model proposed should be continuously utilised to evaluate the project management maturity of Eskom on an ongoing basis; there should be a significant cultural change and a project management office should be established.
Thesis (M.Com. (Business Management)) -- University of Limpopo, 2020
Keywords: Project management maturity; Eskom; Electricity; Project Management; Project Management Maturity Model